COVID-19 and diabetes: What do we know so far?. Issue 15 (August 2022) - Gangadaran, Prakash; Padinjarathil, Himabindu; Rajendran, Shri Hari Subhashri; Jogalekar, Manasi P; Hong, Chae Moon; Aruchamy, Baladhandapani; Rajendran, Uma Maheswari; Gurunagarajan, Sridharan; Krishnan, Anand; Ramani, Prasanna; Subramanian, Kavimani
Coronavirus disease 2019 (COVID-19) management has been challenging for patients with comorbidities. Patients with diabetes and COVID-19, in particular, have shown severe symptoms and rapid progression of the disease. They also have a high mortality rate compared to the non-diabetic population. The high mortality rate is caused in people with diabetes who are in a pro-inflammatory condition; this could worsen COVID-19. In addition, people with diabetes have circulatory issues and COVID-19 infection can lead to further clotting problems. It is critical to understand the mechanisms underlying the adverse clinical outcomes in patients with diabetes and COVID-19. This review discusses various disease conditions contributing to poor prognosis in diabetic COVID-19 patients such as hyperglycemia, insulin resistance, impaired pancreatic function, and production of advanced glycation end products.